Measuring the effects of bronchial thermoplasty using oscillometry. Issue 5 (12th November 2018) - Langton, David; Ing, Alvin; Sha, Joy; Bennetts, Kim; Hersch, Nicole; Kwok, McKinny; Plummer, Virginia; Thien, Francis; Farah, Claude
ABSTRACT: Background and objective: Bronchial thermoplasty (BT) has been consistently shown to reduce symptoms, exacerbations and the need for reliever medication in patients with severe asthma. Paradoxically, no consistent improvement in spirometry has been demonstrated. It has been suggested that this is due to a reduction in peripheral resistance in small airways, not captured by spirometry. Therefore, in this study, we evaluate the response to BT using oscillometry. Methods: A total of 43 patients with severe asthma from two centres were evaluated at baseline, 6 weeks and 6 months post BT, using spirometry, plethysmography and oscillometry, in addition to medication usage, exacerbation frequency and the Asthma Control Questionnaire (5‐item version) (ACQ‐5). Results: The mean age was 58.4 ± 11.2 years, forced expiratory volume in 1 s (FEV1 ) 55.5 ± 20.1% predicted, forced expiratory ratio 53.0 ± 14.5% and FEV1 response to salbutamol was 14.0 ± 14.5%. Following BT, the group responded to treatment with an improvement in ACQ‐5 from 2.9 ± 0.9 at baseline to 1.7 ± 1.1 at 6 months ( P < 0.005). There was an 81% reduction in exacerbation frequency ( P < 0.001) and 50% of patients were weaned completely from maintenance oral corticosteroids. No changes after treatment were observed in spirometry but the residual volume reduced from 147 ± 38% to 139 ± 39% predicted ( P < 0.01). Baseline oscillometry demonstrated high levels of resistance at 5 Hz with normal resistance at 20 Hz, indicating resistance in the small airways was elevated, but no changes were observed in any oscillometry parameter after BT treatment. Conclusion: Lung impedance measured with oscillometry did not change following BT despite marked clinical improvements in patients with severe asthma. Abstract : Oscillometry was used to examine the effects of bronchial thermoplasty on the small airways of 43 patients with severe asthma. No significant effects were demonstrated. See related Editorial